An exploration of the mental health and well-being of postgraduates in pharmacy and pharmaceutical science programs. - Wash, Andrew; Hastings, Tessa J.; Murugappan, Meena N.; Watterson, Taylor L.; Murry, Logan T. (Journal of the American Pharmacists Association: JAPhA, 2022)
Background: Postgraduate students enrolled at colleges and schools of pharmacy are at an increased risk of experiencing difficulties with mental health and well-being; however, there is minimal work exploring mental health and well-being among postgraduates in pharmacy and pharmaceutical science programs.Objectives: (1) to explore the current mental health and well-being of pharmacy postgraduates, (2) to identify factors that promote and hinder mental well-being at the individual and organizational levels, and (3) to explore perspectives regarding organizational priorities, resources, and support tools that may improve the mental health and well-being of postgraduates in pharmacy and pharmaceutical science programs.Methods: This study conducted a cross-sectional survey of postgraduates in pharmacy and pharmaceutical science programs. Surveys were distributed electronically via the American Pharmacists Association's (APhA) broadcast e-mail system to postgraduate members and through the professional networks of APhA Academy of Pharmaceutical Research and Science (APhA-APRS) Postgraduate Advisory Committee members. The survey had 3 sections: demographics, current mental health and well-being status, and barriers and facilitators to mental health and well-being. Descriptive statistics and frequencies were generated for quantitative survey responses. Open-ended responses were categorized and presented with each question.Results: Fifty-one responses were analyzed. The sample had a mean age of 29.0 ± 6.6 years, included 58.8% women or womxn, and most were in doctoral programs (58.8%) for 2.3 ± 2.7 years in various disciplines. There were 27.5% of respondents categorized as having flourishing mental health and 7.8% with languishing mental health. Factors such as practicing self-care or engaging in hobbies (94.1% for each) were most commonly rated as having a positive impact on well-being, and societal racism and discrimination (66.7%) was most commonly reported as having a negative effect on well-being. Top priorities for postgraduates included work-life balance, career prospects, meaningful relationships, and financial concerns.Conclusion: There are a number of organizational and institutional priorities that may improve pharmacy and pharmaceutical science graduate students' mental health and well-being.